Correlações entre a Política Nacional de Alfabetização (PNA - 2019) e o Relatório Alfabetização Infantil (2007): há novos caminhos? - Bernardino, Verônica Santana Epifânio (2023)
The objective of this research is to compare the texts of the National Literacy Policy (PNA) and the Final Report of the Working Group (GT) established by the Chamber of Deputies, entitled Children's Literacy: new paths, in order to understand the conception of language and the concepts of literacy adopted in both documents, as well as the method indicated for adoption in Brazilian schools. It is relevant to analyze these documents and their correlations because our social, political, and historical reality is permeated by intense debates about literacy and its constitutive aspects, both in a theoretical, practical, and methodological bias and in a political-social bias, affecting us positively or negatively in a subjective, collective, and educational scope. Thus, based on the Bakhtinian perspective of language, we take as a presupposition the relevance of dialogue, which constitutes the self and the other in uninterrupted discourses, with dialogue having a political dimension in the construction of people's consciousness, as emphasized by Fiorin (2009). Following this perspective, we conducted a documentary research with a qualitative approach, understanding, through texts/documents, the text as immediate reality (Bakhtin, 2011), how literacy policies were/are being thought and implemented, taking into account the discourses that surround reality and the way literacy has been discussed/dialogued. This contributes to the construction of an excess of vision in relation to the contemporary context, seeking, in social and educational scopes, incessant resistance to possible policies of regression and anti-democracy.